2015
DOI: 10.1128/aac.04541-14
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Characterization of Pyrazinamide Resistance among Multidrug-Resistant Mycobacterium tuberculosis Isolates in Zhejiang, China

Abstract: e To explore the phenotypic and genotypic characterization of pyrazinamide (PZA) resistance among multidrug-resistant Mycobacterium tuberculosis (MDR-TB) isolates in Zhejiang province, a total of 274 MDR-TB isolates were collected. Drug susceptibility testing and spoligotyping were performed on all clinical isolates. In addition, the mutated features of PZA-resistant loci, including pncA and rpsA, were also analyzed by DNA sequencing. Our results showed that the prevalence of PZA resistance among MDR-TB strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
53
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 33 publications
13
53
4
Order By: Relevance
“…PZA susceptibility testing by Bactec MGIT 960 revealed that 16.7% (147/878) of the studied patients were PZA resistant. Simultaneously, a higher level of PZA resistance (30.2% [39/129]) was found in the MDR-TB isolates, which is consistent with previously reported studies with PZA resistance proportions ranging from 36% to 54% among MDR-TB patients (18)(19)(20). A significantly higher proportion of PZA resistance was observed in MDR cases than in first-line drugsusceptible cases (30.2% versus7.7%; P Ͻ 0.001).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…PZA susceptibility testing by Bactec MGIT 960 revealed that 16.7% (147/878) of the studied patients were PZA resistant. Simultaneously, a higher level of PZA resistance (30.2% [39/129]) was found in the MDR-TB isolates, which is consistent with previously reported studies with PZA resistance proportions ranging from 36% to 54% among MDR-TB patients (18)(19)(20). A significantly higher proportion of PZA resistance was observed in MDR cases than in first-line drugsusceptible cases (30.2% versus7.7%; P Ͻ 0.001).…”
Section: Discussionsupporting
confidence: 80%
“…In contrast to earlier hospital-based studies or those conducted in a single region in China (18), the present study was multicenter, to better understand the epidemiological situation of PZA resistance across China. This is the first reported population-based study of PZA resistance among TB cases in China.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, it should be noted that the proportion of MDR tuberculosis with PZA resistance has reached 50.0% (versus 11.3% in non-MDR TB) in China, which is consistent with a report from Zhejiang Province in China (43.1%) (32). Numerous lines of evidence demonstrate that MDR-TB is more likely to acquire resistance to PZA, which may be correlated with a higher frequency of developing pncA mutations conferring PZA resistance after the acquisition of both RIF and INH resistance (33).…”
Section: Discussionsupporting
confidence: 78%
“…Given the high likelihood of frameshift mutations resulting in resistance and the high specificity (94%–98%) of pncA SNPs for pyrazinamide resistance ( 13 , 14 ), we estimate that at least 56%–66% of MDR TB and 90%–95% of XDR TB cases from these settings are likely to be resistant to pyrazinamide. Only a small number of mutations were synonymous, previously associated with pyrazinamide susceptibility, or had an SNP for which phenotypic susceptibility has not been previously tested.…”
Section: Discussionmentioning
confidence: 99%